Small Renal Masses: Incidental Diagnosis, Clinical Symptoms, and Prognostic Factors - F. M. Sánchez-Martín; F. Millán-Rodríguez; G. Urdaneta-Pignalosa; J. Rubio-Briones; H. Villavicencio-Mavrich (Advances in Urology)
Introduction. The small renal masses (SRMs) have increased over the past two decades due to more liberal use of imaging techniques. SRMs have allowed discussions regarding their prognostic, diagnosis, and therapeutic approach. Materials and methods. Clinical presentation, incidental diagnosis, and prognosis factors of SRMs are discussed in this review. Results. SRMs are defined as lesions less than 4 cm in diameter. SRM could be benign, and most malignant SMRs are low stage and low grade. Clinical symptoms like hematuria are very rare, being diagnosed by chance (incidental) in most cases. Size, stage, and grade are still the most consistent prognosis factors in (RCC). An enhanced contrast SRM that grows during active surveillance is clearly malignant, and its aggressive potential increases in those greater than 3 cm. Clear cell carcinoma is the most frequent cellular type of malign SRM. Conclusions. Only some SRMs are benign. The great majority of malign SRMs have good prognosis (low stage and grade, no metastasis) with open or laparoscopic surgical treatment (nephron sparing techniques). Active surveillance is an accepted attitude in selected cases.